A Legal Comparison Of Informed Consent And A Conceptual Analysis Of Doctor Protection In Medical Practice In Indonesia - Dhanudibroto, Handojo; Heliany , Ina (Ridwan Institute, 2025)
The increasing number of patient complaints to the Professional Disciplinary Council on doctors is something that needs to be considered. Patient complaints received by the Professional Disciplinary Council are closely related to deviations in medical management standards that are detrimental to patients. One of the important things in carrying out medical service management carried out by doctors is informed consent and informed refusal which are absolutely necessary before carrying out medical actions. In this writing, the author conducts a conceptual analysis and legal comparison of informed consent and informed refusal from several countries that require both consents, with the consideration that the countries being compared have carried out medical practices that are among the best in the world. Then in the writing will be explained the potential for medical actions by doctors that can be categorized as medical fraud along with their handling. The research method in this writing uses the normative juridical method with primary, secondary and tertiary legal materials and comparative law in the Anglo-Saxon and continental European legal traditions. In addition, a comparative study of Indonesian positive law was also conducted in this case general law (jure generali) which overlaps and special health law (jure specialis) along with its implementing regulations.